Deuterated buprenorphine retains pharmacodynamic properties of buprenorphine and resists metabolism to the active metabolite norbuprenorphine in rats - Janganati, Venumadhav; Salazar, Paloma; Parks, Brian J.; Gorman, Gregory S.; Prather, Paul L.; Peterson, Eric C.; Alund, Alexander W.; Moran, Jeffery H.; Crooks, Peter A.; Brents, Lisa K. (Frontiers in Pharmacology, 2023)
An active metabolite of buprenorphine (BUP), called norbuprenorphine (NorBUP), is implicated in neonatal opioid withdrawal syndrome when BUP is taken during pregnancy. Therefore, reducing or eliminating metabolism of BUP to NorBUP is a novel strategy that will likely lower total fetal exposure to opioids and thus improve offspring outcomes. Precision deuteration alters pharmacokinetics of drugs without altering pharmacodynamics. Here, we report the synthesis and testing of deuterated buprenorphine (BUP-D2). We determined opioid receptor affinities of BUP-D2 relative to BUP with radioligand competition receptor binding assays, and the potency and efficacy of BUP-D2 relative to BUP to activate G-proteins via opioid receptors with [35S]GTPγS binding assays in homogenates containing the human mu, delta, or kappa opioid receptors. The antinociceptive effects of BUP-D2 and BUP were compared using the warm-water tail withdrawal assay in rats. Blood concentration versus time profiles of BUP, BUP-D2, and NorBUP were measured in rats following intravenous BUP-D2 or BUP injection. The synthesis provided a 48% yield and the product was ≥99% deuterated. Like BUP, BUP-D2 had sub-nanomolar affinity for opioid receptors. BUP-D2 also activated opioid receptors and induced antinociception with equal potency and efficacy as BUP. The maximum concentration and the area under the curve of NorBUP in the blood of rats that received BUP-D2 were over 19- and 10-fold lower, respectively, than in rats that received BUP. These results indicate that BUP-D2 retains key pharmacodynamic properties of BUP and resists metabolism to NorBUP and therefore holds promise as an alternative to BUP.